A 3-D Simulation and Experimental Study of Cutting Forces in Turning Inconel-718. (2017) - Kumar, Mechiri Sandeep; Reddy, S. Rajashekhar; Vasu, V.
Abstract: Force measurement in metal cutting is an essential requirement as it is related to machine part design, tool design, power consumptions, vibrations, part accuracy, etc. It is the purpose of the measurement of cutting force to be able to understand the cutting mechanism such as the effects of cutting variables on the cutting force, the machinability of the work piece, the process of chip formation, chatter and tool wear. This paper presents a simulation model for estimation of cutting forces in turning process. A 3D simulation model was used for predicting the cutting forces as it is more nearer to practical process than the two-dimensional model, although computing time is very large for a 3D model. A 3D model for oblique cutting is used and model to analyze turning of Inconel 718 using a TiAlN coated carbide inserts was developed using ABAQUS software. The finite element analysis incorporated the elastic and plastic properties of the work material in machining and Johnson-cook model is used for cutting simulation. The results from simulation model were compared with experimental data. A Taguchi's L9 orthogonal array was used for the experimental runs. It is found that simulation results were in good agreement with experimental results.